Queers, Cupid’s Arrow, and Contradictions in the Classroom: An Activity Theory Analysis - Heather Trahan (Journal of the Assembly for Expanded Perspectives on Learning, 2012)
“Third generation” activity theory can help instructors support and also deal with gay romance in the classroom.